First reported case of infective endocarditis caused by community-acquired methicillin-resistant Staphylococcus aureus not associated with healthcare contact in Brazil - Fortes,Claudio Querido (2008)
We report here the first case of endocarditis due to CA-MRSA not associated with healthcare contact in Brazil in Brazil. A previously healthy patient presented with history of endocarditis following a traumatic wound infection. Patient had multiple positive blood cultures within 72 h of admission and met modified Duke's criterion for infective endocarditis. The isolate was typed as Staphylococcal cassette chromosome (SCC) mec type IV and was positive for presence of Panton-Valentine leukocidin (PVL). Increased incidence of CA-MRSA endocarditis is a challenge for the internist to choose the best empirical therapy. Several authors have suggested an empirical therapy with both a beta-lactam and an anti-MRSA agent for serious S. aureus infections. Our patient was treated with Vancomycin and made complete recovery in 3 months.